PHB/PZT composite - Malmonge, J. A. [UNESP]; Okajima, L. H. [UNESP]; Malmonge, L. F. [UNESP]; Sakamoto, W. K. [UNESP]; Malmonge, S. M. (Institute of Electrical and Electronics Engineers (IEEE), 2005)
Flexible standing films of piezoelectric composite made of lead zirconate titanate (PZT) ceramic powder and Poly(3-hydroxybutyrate) (PHB) in powder form were obtained by mixing both polymers mechanically and pressed at 180°C. The piezoelectric coefficient d33 were investigated as function of PZT content, poling temperature and electric field. The highest value for d 33 coefficient was around 6pC/N for 50 vol% of PZT content in the composite. As PHB is a biodegradable polymer the composite has potential application as sensor minimizing the environmental problems.
Keywords: Biodegradable polymers; Composite materials; Electric fields; Lead compounds; Polymer films; Ceramic powder; Lead zirconate titanate (PZT); Piezoelectric coefficient; Poling temperature; Piezoelectric ceramics